Author Correction: Solar superstorm of AD 774 recorded subannually by Arctic tree rings - Uusitalo, J.; Arppe, L.; Hackman, T.; Helama, Samuli; Kovaltsov, G.; Mielikäinen, K.; Mäkinen, Harri; Nöjd, Pekka; Palonen, V.; Usoskin, I.; Oinonen, M.
Article number 1292 2019